Standardisation of rooting media for propagation of vanilla (Vanilla planifolia Andr.) - M R SUDHARSHAN, V KRISHNAKUMAR, SIDDAGANGAIAH SIDDAGANGAIAH, B A VADIRAJ (Journal of Spices and Aromatic Crops, 1996)
Evaluation of various rooting media indicated that vermicompost and decomposed coir pith were ideal for rooting and multiplication of vanilla (Vanilla planifolia).